2019
DOI: 10.5430/ijfr.v10n6p283
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Total Quality Management on University Performance in Jordan

Abstract: Total Quality Management (TQM) a functioning idea to accomplish incessant performance improvement-is the word of mouth of the 1990s, attracting deep interest among organizations and educational institutions in many countries. Numerous policy-makers truly believe that TQM can improve the performance of their organizations but they did not test it to make sure the effect of TQM. Hence, the purpose of this study is to examine the effect of TQM on university performance in Jordan. This relationship obtains a subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
(26 reference statements)
2
4
0
Order By: Relevance
“…The research examined all assumptions on the quality of education and its main factors. The results showed the relationship between the effectiveness of education and the education quality management system [31]. In present research found that education quality management factors lead to student academic success.…”
Section: Figure 1 Analysis Of Average Academic Performance Scoressupporting
confidence: 51%
“…The research examined all assumptions on the quality of education and its main factors. The results showed the relationship between the effectiveness of education and the education quality management system [31]. In present research found that education quality management factors lead to student academic success.…”
Section: Figure 1 Analysis Of Average Academic Performance Scoressupporting
confidence: 51%
“…The Z generation, or the Internet generation, was literally born with a smartphone in hand; Known for their laziness and smartphone addiction, this generation is changing the business world in general. A generation that loves creativity and innovation is highly risk-averse and has indescribable skills in online searches and research (Ahmad et al, 2019;Alzeaideen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…By hiring them, these shareholders signal that they protect the public shareholders by providing qualified financial reports. This explanation is confirmed by Alzeaideen and Al-Rawash (2018), Gerged et al (2020), and Ngo et al (2020, concluding the positive tendency of institutional proprietorship to use reputable auditors. By indicating these elucidations, this study proposes the first hypothesis (H1): Institutional proprietorship stimulates the propensity of the company to hire a respected auditor.…”
Section: Introductionmentioning
confidence: 66%
“…The studies investigating the tendency determinants of choosing public accounting linked to the big four auditors are numerous, such as those carried out by Al-Hajri (2018), Alzeaideen and Al-Rawash (2018), Al-Hajaya (2019), Septiana and Khafid (2019), Sulistyawati and Agustina (2019), Gerged et al (2020), and Ngo et al (2020), Corten et al (2021), and Thu and Khanh (2022). Based on their research, at the least possible, three contributing factors exist, i.e., institutional proprietorship and committee audit size becoming the primary variable and company size as the control variable.…”
Section: Introductionmentioning
confidence: 99%